Finger millet (Eleusine coracana) improvement: Challenges and prospects-A review - Gebreyohannes, Adane; Shimelis, Hussein; Mashilo, Jacob; Odeny, Damaris A.; Tadesse, Taye; Ojiewo, Chris O. (Wiley, 2024)
Finger millet is a climate-resilient and highly nutritious small grain crop widely grown in the semi-arid tropics. It has multiple uses, including for food, feed and beverage preparations. However, finger millet is an under-utilized and under-researched crop with a mean yield of <1.0 t/ha despite a potential productivity of up to 8 t/ha. The yield gap is attributed to several production constraints, such as biotic and abiotic stresses, a lack of access to improved seeds and production inputs and poor agronomic management practices. There are valuable genetic resources and genetic variability of finger millet in its centres of diversity and global gene banks for variety design, product development and commercialization. The genetic variability can be harnessed further to integrate essential traits into candidate varieties through conventional and modern breeding methods. Breeding and genetic innovations such as genomics-assisted breeding, mutation breeding and genome editing would accelerate finger millet breeding and new variety design and deployment. The objective of this review was to document the opportunities, challenges and prospects of finger millet improvement as a guide for variety development and deployment with enhanced grain yield and nutritional contents. The first section describes global production status and yield gains, major production and productivity challenges in finger millet. This is followed by an in-depth presentation on breeding and genetic progress on variety development with improved agronomic and nutritional quality traits, drought and salinity tolerance, and fungal diseases, weeds and insect pest resistance. Further, the review summarized finger millet's genetic and genomic resources, reference genomes, whole genome re-sequencing and transcriptomics of finger millet technologies, genetic engineering and genome editing and their integration with conventional breeding methods for variety design with desired end-use traits. The review provides foundational information to expedite the development of new-generation finger millet cultivars with desirable product profiles, including high grain yield potential, early maturity, desirable seed colour, compact head type, food and feed nutrients quality and high marketability through modern breeding approaches.